Part-time work, gender and job satisfaction: Evidence from a developing country - Florencia López Bóo; Lucia Madrigal; Carmen Pagés (Inter-American Development Bank, Research Department, 2009)
This paper investigates the relationship between part-time work and job satisfaction using a recent household survey from Honduras. In contrast to previous work for developed countries, this paper does not find a preference for part-time work among women. Instead, both women and men tend to prefer fulltime work, although the preference for working longer hours is stronger for men. Consistent with an interpretation of working part-time as luxury consumption, the paper finds that partnered women with children, poor women or women working in the informal sector are more likely to prefer full-time work than single women, partnered women without children, non-poor women or women working in the formal sector. These results have important implications for the design of family and child care policies in low-income countries.
Keywords: C13; J16; J28; 330; Job Satisfaction; Gender; Part-time work; Job Flexibility; Teilzeitarbeit; Weibliche Arbeitskräfte; Arbeitszufriedenheit; Arbeitszeit; Familienpolitik; Honduras; Niedriglohnländer